Policy Analysis of the Sports Achievement Development Program in Papua Following the conclusion of the XX National Sports Week (PON)as assessed by DISORDA Papua - Wasa, Carolus; Rahayu, Tandiyo; Setijono, Hari; Hartono, Mugiyo (Journal of Physical Education and Sports, 2024)
Examining the strategies for the advancement of sports development in Papua following the XX National Sports Week (PON) based on the perspective of DISORDA Papua is crucial as sports development must be carried out in a methodical, measurable, and continuous manner. This study aims to assess the policies of sports development programs in Papua post the XX PON. It utilizes qualitative methods involving interviews, observations, and documentation for data collection. The policy analysis methodology employed includes problem formulation, forecasting, recommendations, monitoring, and evaluation. The study involved 5 participants from the Indonesian National Sports Committee (KONI) Papua. The research findings indicate that the sports development program policy in Papua following PON XX demonstrates that the province's sports development program has not been effectively integrated. In general, the policy in Papua Governor Regulation Number 29 of 2020 concerning the Description of Duties and Functions of the Papua Province Sports and Youth Service reveals that the sports development program in Papua province is not yet well integrated.